1,25-dihydroxyvitamin D and PTHrP mediated malignant hypercalcemia in a seminoma - Rodríguez Gutiérrez, René; Zapata Rivera, María Azucena; Quintanilla Flores, Dania Lizet; Camara Lemarroy, Carlos Rodrigo; Lavalle González, Fernando Javier; González González, José Gerardo; Villarreal Pérez, Jesús Zacarías (2014)
Background: Seminomas have been rarely associated with malignant hypercalcemia. The responsible mechanism of hypercalcemia in this setting has been described to be secondary to 1,25-dihydroxyvitamin D secretion. The relationship with PTHrP has not been determined or studied. The aim of this study is to describe and discuss the case and the pathophysiological mechanisms involved in a malignant hypercalcemia mediated by 1,25-dihydroxyvitamin D and PTHrP cosecretion in a patient with seminoma. Case presentation: A 35-year-old man was consulted for assessment and management of severe hypercalcemia related to an abdominal mass. Nausea, polyuria, polydipsia, lethargy and confusion led him to the emergency department. An abdominal and pelvic enhanced CT confirmed a calcified pelvic mass, along with multiple retroperitoneal lymphadenopathy. Chest x-ray revealed “cannon ball” pulmonary metastases. The histopathology result was consistent with a seminoma. Serum calcium was 14.7 mg/dl, PTH was undetectable, 25-dihydroxyvitamin D was within normal values and PTHrP and 1,25 dihydroxyvitamin were elevated (35.0 pg/ml, and 212 pg/ml, respectively). After the first cycle of chemotherapy with bleomycin, etoposide and cisplatin, normocalcemia was restored. Both PTHrP and 1,25-dihydroxyvitamin D, dropped dramatically to 9.0 pg/ml and 8.0 pg/ml, respectively. Conclusion: The association of seminoma and malignant hypercalcemia is extremely rare. We describe a case of a patient with a seminoma and malignant hypercalcemia related to paraneoplastic cosecretion of 1,25-dihydroxyvitamin D and PTHrP. After successful chemotherapy, calcium, PTHrP and 1,25-Dihydroxyvitamin D returned to normal values.